Beyond structure: ultrafast X-ray absorption spectroscopy as a probe of non-adiabatic wavepacket dynamics. (19th September 2016) - Neville, Simon P.; Averbukh, Vitali; Patchkovskii, Serguei; Ruberti, Marco; Yun, Renjie; Chergui, Majed; Stolow, Albert; Schuurman, Michael S.
Abstract : The excited state non-adiabatic dynamics of polyatomic molecules, leading to the coupling of structural and electronic dynamics, is a fundamentally important yet challenging problem for both experiment and theory. Ongoing developments in ultrafast extreme vacuum ultraviolet (XUV) and soft X-ray sources present new probes of coupled electronic-structural dynamics because of their novel and desirable characteristics. As one example, inner-shell spectroscopy offers localized, atom-specific probes of evolving electronic structure and bonding ( via chemical shifts). In this work, we present the first on-the-fly ultrafast X-ray time-resolved absorption spectrum simulations of excited state wavepacket dynamics: photo-excited ethylene. This was achieved by coupling the ab initio multiple spawning (AIMS) method, employing on-the-fly dynamics simulations, with high-level algebraic diagrammatic construction (ADC) X-ray absorption cross-section calculations. Using the excited state dynamics of ethylene as a test case, we assessed the ability of X-ray absorption spectroscopy to project out the electronic character of complex wavepacket dynamics, and evaluated the sensitivity of the calculated spectra to large amplitude nuclear motion. In particular, we demonstrate the pronounced sensitivity of the pre-edge region of the X-ray absorption spectrum to the electronic and structural evolution of the excited-state wavepacket. We conclude that ultrafast time-resolved X-ray absorption spectroscopy may become a powerful tool in the interrogation of excited state non-adiabatic molecular dynamics.